Sonho e pecado: visões oníricas e oniromancia dos "índios" e "gentios" na catequese jesuítica na América Portuguesa (1549-1618) - Lima, Luís Filipe Silvério (Revista de História, 2003)
Analyzing 16th and early 17th Century Jesuit's letters and manuals of confession, this paper explores the Jesuitical view of the Indians belief in dreams in Portuguese America. The central aim is to understand how the European rhetorical models, the concept of sin and modern dream theories interfered in the descriptions of the natives' belief in dreams.